On the dynamics of free and excited oscillations of a simple portal frame foundation - Dantas, MJH; Balthazar, José Manoel [UNESP] (Elsevier B.V., 2006)
In this paper we search for the dynamics of a simple portal structure in the free and in the periodic excitation cases. By using the Center Manifold approach and Averaging Method, we obtain results on both stability and bifurcation of equilibrium points and periodic orbits. (C) 2005 Elsevier Ltd. All rights reserved.
Keywords: stability; bifurcation; center manifolds; averaging method; hyperbolic periodic orbits